PENGARUH PEMBERIAN BUBUR KACANG HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL DI DESA PSR IV NAMU TERASI KECAMATAN SEI BINGAI KABUPATEN LANGKAT TAHUN 2019 - Krisna, Putri; Hutabarat, Julietta; Desfauza, Evi (Poltekkes Kemenkes Medan, 2019)
Introduction: Anemia prevalence Indonesia in 2018 reaches 48.9% (Baritbankes, 2018). 100 grams of green beans is contained 6.7 mg of iron serves to increase Hb levels and 6.9 mg of vitamin C serves to help iron absorption. Consuming 200 gr of green beans per day can meet almost 50% of the iron needs of pregnant women (Tuhana Taufiq, 2004). This study aims to determine the effect of green bean porridge on increasing Hb levels of pregnant women in Pasar IV the Village of Namu Terasi, Sei Bingai Subdistrict, Langkat Regency 2019. Methods: This study was a Pre-experiment study designed with the design of one group pretest-posttest and where 11 pregnant mothers of Trimester II were used as research samples taken through purposive sampling technique. Results and Discussion: Through the Paired Simples test the T-test obtained the value of ? (0.01) <? (0.05), which means that green bean porridge proved to significantly increase the Hb levels of pregnant women. The mean of Hb level of pregnant women before given green bean porridge was 10.9 gr / dl to 1.26, and the mean became 11.9 gr / dl to 0.93 after being given green bean porridge, it is found an increase in mean Hb levels before and after the treatment 1.01 gr / dl to 1.02 gr / dl. .Conclusion: Green bean porridge has the effect of increasing Hb level in pregnant women. Health workers are expected to encourage every pregnant woman to consume green bean porridge as an supplementary food.